Value of Fungicide Application in Wheat Production in Southwest Kansas - A. J. Foster; R. Lollato; M. Vandeveer; E. D. De Wolf (Kansas Agricultural Experiment Station Research Reports, 2017)
During the past several years, applying fungicide to wheat has become a more common practice. The availability of cost-effective generic fungicides, as well as the positive yield responses often reported, seem to be the potential drivers for the adoption of such practices by producers. We conducted a wheat fungicide trial in Garden City, KS, to answer the following questions: 1) Do fungicide applications pay? And 2) Can remote sensing technology be used to quantify the efficacy of different fungicide products? The study consisted of two wheat varieties sown on September 29, 2015 (Oakley CL, highly resistant to stripe rust; and TAM 11, highly susceptible to stripe rust), different fungicide products and different times of application. Stripe rust was the major fungal disease impacting wheat yield in southwest Kansas in 2015-16. Fungicide application increased grain yield over the control for all fungicide products. The greatest grain yield resulted from the application of Tebustar. These results suggest that there could be some potential benefits to early season application of fungicide in southwest Kansas, although the majority of the grain yield gain comes from the flag leaf application. Additional years of data are required to make more robust, meaningful interpretations.
Keywords: remote sensing; stripe rust; fungicide; wheat